Plasticity of 3D Hydrogels Predicts Cell Biological Behavior - Malandrino, Andrea; Zhang, Huijun; Schwarm, Nico; Böhringer, David; Kah, Delf-Thorge Eric; Kuster, Christian; Boccaccini, Aldo R.; Fabry, Ben (Biomacromolecules, 2024)
Under 3D culture conditions, cells tend to spread, migrate, and proliferate better in more viscoelastic and plastic hydrogels. Here, we present evidence that the improved cell behavior is facilitated by the lower steric hindrance of a more viscoelastic and plastic matrix with weaker intermolecular bonds. To determine intermolecular bond stability, we slowly insert semispherical tipped needles (100-700 μm diameter) into alginate dialdehyde-gelatin hydrogels and measure stiffness, yield strength, plasticity, and the force at which the surface ruptures (puncture force). To tune these material properties without affecting matrix stiffness, we precross-link the hydrogels with CaCl2 droplets prior to mixing in NIH/3T3 fibroblasts and final cross-linking with CaCl2. Precross-linking introduces microscopic weak spots in the hydrogel, increases plasticity, and decreases puncture force and yield strength. Fibroblasts spread and migrate better in precross-linked hydrogels, demonstrating that intermolecular bond stability is a critical determinant of cell behavior under 3D culture conditions.
CRIS-Team Scopus Importer:2025-02-04